A cross sectional study on the frequency of thyroid disorders in pregnancy and the asssociated obstetric complications - K. , Sreelakshmy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Thyroid disorders have a yet unclear impact on obstetric complications. The studies have been varied and mostly contradictory. The aim of the study was to examine the pattern of thyroid disorders and its obstetric complications. Methods: This cross-sectional study enrolled 334 pregnant women of less than 12 weeks of gestation. After routine clinical and ultrasound evaluation of all cases, all baseline investigations and TSH was done. In all cases with low TSH free T3 and free T4 was done. All patients were followed up till delivery and the obstetric events were recorded. The data collected were analysed using chi-square test. Results: Of the 334 enrolled the data on pregnancy related events were available for 276 patients. Subclinical hypothyroidism was detected in 10.1% of the population while 3.6% were having overt (clinical) hypothyroidism. Anaemia was more in subclinical hypothyroidism (39.3%) and overt hypothyroidism (40%). Pre-eclampsia was seen 17.85% with subclinical hypothyroidism and 30% with overt hypothyroidism. Eclampsia was seen in 3.7% of subclinical hypothyroidism and 10% of clinical hypothyroidism. Gestational diabetes mellitus (GDM) was more in patients with subclinical hypothyroidism (25%) and overt hypothyroidism (20%). Oligohydramnios and IUGR were higher in the subclinical hypothyroidism (21.42%, 10.7%) and overt hypothyroidism (20%, 10%). There was no difference between the euthyroid, subclinical hypothyroidism and overt hypothyroidism groups with respect to any of the other variables. Conclusions: There was a high frequency of thyroid disorders among pregnant women in our study and this had adverse obstetric consequences.